منصات التمويل الجماعي كآلية لتمويل المؤسسات الناشئة (تجارب دولية) - عبد الرحيم زواد; جلال حوري; مداني موساوي (university of eloued جامعة الوادي, 2025)
"تهدف هذه الدراسة للإجابة على ""إلى أي مدى يسهم التمويل الجماعي في دعم وتمويل المؤسسات الناشئة في الجزائر، وما هي العوائق والفرص التي تواجه هذا النموذج في السياق المحلي؟"" اعتمدت على المنهج الوصفي التحليلي، مع الاستفادة من التجارب الدولية، خاصة تجربة الهند، لتقديم مقترحات قابلة للتطبيق محليًا. توصلت الدراسة إلى أن التمويل الجماعي يمثل آلية واعدة لسد فجوة التمويل الأولي، لكن ضعف الوعي وغياب إطار قانوني ملائم يشكلان أبرز التحديات. كما يمكن الاستفادة من تجربة الهند في تشجيع المستثمرين الملائكيين، وتفعيل دور الجامعات، وتحسين البنية التحتية الرقمية. وأوصت الدراسة بضرورة إدماج أدوات تمويل حديثة ضمن النظام التمويلي الوطني. "This study aims to answer the question, ""To what extent does crowdfunding contribute to supporting and financing startups in Algeria, and what are the obstacles and opportunities facing this model in the local context ?"" It relied on a descriptive and analytical approach, drawing on international experiences, particularly India's, to present locally applicable proposals. The study concluded that crowdfunding represents a promising mechanism for bridging the initial funding gap, but that low awareness and the absence of an appropriate legal framework pose the most significant challenges. The Indian experience can also be leveraged to encourage angel investors, activate the role of universities, and improve digital infrastructure. The study recommended the integration of modern financing tools into the national financing system.
ماستر
Keywords: التمويل الجماعي; المؤسسات الناشئة; تجارب دولية; crowdfunding; startups; international experiences